Concomitant Colon Adenocarcinoma And Tuberculous Lymphadenitis - Arya Abisatya, Albertus Magnus; Prameswari, Ajeng Andini; Fauzi, Agung Rahmat; Febrianto, Aji Pratama; Nugroho, Alexander Steven; Andisari, Hendrata Erry; Harijono, Pandu; Yudadi, Redemptus (RSUP Dr. Kariadi, 2023)
BACKGROUND : Colon involvement in tuberculosis infection is a rare event. The coexistence of colon carcinoma and tuberculous lesions of the colon is less frequently reported. Carcinoma and tuberculosis of the colon can occur at the same site or at different sites. The occurrence of two pathologies at the same site is much less common. CASE PRESENTATION : A 52 year old woman complained of difficulty defecating, an enlarged stomach, pain and decreased appetite and weight loss within one month. On clinical examination, the abdomen appeared convex, slightly distended, and tenderness in the left lower iliac quadrant. Radiological examination supported the diagnose of partial obstructive ileus. The patient was diagnosed with adenocarcinoma of the ascending colon until the hepatic flexura was confirmed through surgery and histopathological examination. On histopathological examination, adenocarcinoma of the colon was found to coexistence with tuberculous lymphadenitis of the colon. CONCLUSION : The etiological and pathophysiological relationship between tuberculous lymphadenitis and colon cancer is still under debate, but surgeons need to be aware of this occurrence, to choose treatment and avoid post-operative worsening.